2010
DOI: 10.4322/actalb.02202007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aquaculture effluents on the growth of Salvinia molesta

Abstract: Objective: Aquaculture generates social and economic benefits, but also causes impacts on the environment. One of the major impacts is the release of untreated effluents into rivers, reservoirs, and lakes, which can affect aquatic populations and communities. In this study, we tested the hypothesis that effluent from aquaculture favors the growth of the floating aquatic macrophyte Salvinia molesta; Methods: The study was carried out in a non-impacted reservoir (NIR) and in another reservoir (IR) that is impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Even considering the small number of replicates (n = 3) and the large standard deviations we observe that the growth curves of the two species in higher and lower nutrient concentrations were similar. However, high nutrient concentrations allow the plants to grow faster and reach high biomass (Thomaz et al, 2007;Pistori et al, 2010). In a reservoir impacted by aquaculture effluent, Pistori et al (2010) reported that S. molesta reached carrying capacity of 36.4 g DM.m -2 after 100 days of experiment, whereas in a non-impacted reservoir the value was 3.0 g DM.m -2 after 200 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even considering the small number of replicates (n = 3) and the large standard deviations we observe that the growth curves of the two species in higher and lower nutrient concentrations were similar. However, high nutrient concentrations allow the plants to grow faster and reach high biomass (Thomaz et al, 2007;Pistori et al, 2010). In a reservoir impacted by aquaculture effluent, Pistori et al (2010) reported that S. molesta reached carrying capacity of 36.4 g DM.m -2 after 100 days of experiment, whereas in a non-impacted reservoir the value was 3.0 g DM.m -2 after 200 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, high nutrient concentrations allow the plants to grow faster and reach high biomass (Thomaz et al, 2007;Pistori et al, 2010). In a reservoir impacted by aquaculture effluent, Pistori et al (2010) reported that S. molesta reached carrying capacity of 36.4 g DM.m -2 after 100 days of experiment, whereas in a non-impacted reservoir the value was 3.0 g DM.m -2 after 200 days. Other authors demonstrated that the growth rates of many species of aquatic macrophytes increase as nutrients availability also increases, but the increase of nutrients concentrations favor the growth of plants up to a certain concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an increase of 400% in phytoplankton biomass and substantial dinoflagellates and chrysophyceae blooms were observed in lake regions close to a trout farm in Canada (Findlay et al, 2009). A recent study revealed that the floating aquatic macrophyte Salvinia molesta biomass (37.4 g dry matter m -2 ) was 12.5 times higher in a reservoir that received aquaculture effluent than the biomass (3.0 g dry matter m -2 ) in the reservoir that was not impacted by the aquaculture activity (Pistori et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We recorded high phytoplankton biovolumes in the inflow water during the first 28 days of the tilapia grow-out period. These high values might be related to the water source, since the inflow water comes from two dams that are oligo-mesotrophic and hypereutrophic and receives effluents from the sectors of fish and frog farming of CAUNESP (Pistori et al, 2010). Furthermore, this period coincided with harvesting in these sectors, when water is rich in nutrients and organic materials are released into the dam.…”
Section: Discussionmentioning
confidence: 99%